Diagnóstico comunitario de salud del barrio San Vicente sector I y III, septiembre-diciembre de 2013 - Saraguro Pacheco, Sandra Janeth (2014)
The present investigation has as main objective to Contribute the invigoration of the PATTERN OF INTEGRAL ATTENTION OF THE COMMUNITY NATIONAL SYSTEM OF FAMILY HEALTH AND INTERCULTURAL in the University Hospital of Motupe, contributing with statistical and data that will allow to the Basic Teams of Health - EAIS (Teams of Integral Attention of Health) to formulate local proposals of health, spread to improve the quality of life of the community of The Band I Lower Sector I. The universe was constituted by 63 families and 260 inhabitants, the present investigation is of descriptive type, in which facts and characteristic related with the population and its environment are detailed, the instrument for the gathering of information was the family record elaborated by MSP and an annex to this record, the interview form allowed to complete the information, it was also analyzed the data, obtaining results that they will serve as base line. Between the most relevant data include: that the most prevalent sex is male, the level of outstanding education is the High School, 6 Illiterate some of whom are heads of households were found, as schoolchildren and adolescents are in a good nutritional state in regard to sexually active women, the rhythm method is the most widely used family planning. In the epidemiological profile include the Hypertension is the most prevalent chronic disease affecting ages 20-64 years between degenerative diseases found cancer, and with regard to the most outstanding physical disabilities is disabled. Keywords: Community Diagnostics, Health, Situation